2023
DOI: 10.4274/archepilepsy.2023.224168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antiepileptic Drug Sodium Valproate on Stomach Tissue Glycoproteins: The Protective Role of Moringa Extract

Umar Faruk Magaji,
Syhejla Miftari,
Özlem Saçan
et al.

Abstract: Objective: Sialic acid, hexoses, hexosamines and fucose are components of glycoprotein, glycolipid and/or ganglioside. These glycoconjugates are essential components of cellular membrane and receptors, which are required for normal cellular activities. The levels of these aforementioned glycans are likely to be obstructed under biological conditions (such as oxidative stress) that leads to cellular and tissue damage. Despite the efficacy of valproate as a broad-spectrum antiepileptic drug, it administration is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…[32] In another report by Magaji et al, it was shown that moringa had a powerful antioxidant capacity by scavenging nitrite and N,N-dimethyl-pphenylenediamine (DMPD + ) radicals, and also showed ferric reducing power. [65] Thus, it can be suggested that the inhibition of α-amylase, maltase, and LDH in all salivary glands of the VM group may be related to the antioxidant activity of moringa. ACP and ALP are enzymes that hydrolyze organophosphates at different pH levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] In another report by Magaji et al, it was shown that moringa had a powerful antioxidant capacity by scavenging nitrite and N,N-dimethyl-pphenylenediamine (DMPD + ) radicals, and also showed ferric reducing power. [65] Thus, it can be suggested that the inhibition of α-amylase, maltase, and LDH in all salivary glands of the VM group may be related to the antioxidant activity of moringa. ACP and ALP are enzymes that hydrolyze organophosphates at different pH levels.…”
Section: Resultsmentioning
confidence: 99%
“…Ertik et al., showed that moringa extract was a potent inhibitor of LDH both in vitro and in vivo in VA‐induced muscle injury [32] . In another report by Magaji et al., it was shown that moringa had a powerful antioxidant capacity by scavenging nitrite and N,N‐dimethyl‐p‐phenylenediamine (DMPD + ) radicals, and also showed ferric reducing power [65] . Thus, it can be suggested that the inhibition of α‐amylase, maltase, and LDH in all salivary glands of the VM group may be related to the antioxidant activity of moringa.…”
Section: Resultsmentioning
confidence: 99%